RANCANG BANGUN SISTEMMONITORING KADAR SALINITAS AIR MENGGUNAKAN WIRELESS SENSOR SYSTEMS (WSS) - Febriana Tirta Kirana; Suryono Suryono (Youngster Physics Journal, 2016)
Real time monitoring in designated location using remote observation has become one topic chosen to be efficiently developed because it can be observed and anticipated earlier when the water quality is decreasing. One of the indicators of water quality is salinity, which is being developed through this study by using remote measurement system (telemetry) using Wi-Fi network. To determine the change of the indicator, a salinity sensor was used to determine the level of salinity. The sensors were mounted on a Remote Terminal Unit (RTU) attach on the object being observed. Those sensors produced analog signal so the signal should be converted into digital signal using Analog to Digital Converter (ADC) on ATSAM3X8E microcontroller. The digital data were then sent using serial communication from microcontroller to computer. The data were saved in the database and sent to Control Terminal Unit (CTU) using Wi-Fi network. A characterization was then conducted to a series of sensors produced from the previous phase using standard equipment to ADC value and a formula of sensor characteristic to ADC value was calculated which results in salinity equation value on y = 0,049 x – 35,306. The formula was then used in microcontroller program which results in coefficient of correlation on salinity sensor as R = 0,993 with 0,025 ppt error. From the test on communication system between database in Remote Terminal Unit (RTU) and Control Terminal Unit (CTU), there is no additional and missing data from data sent and data received, so it can be concluded that there is no error.